2022
DOI: 10.2196/29594
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes, Measurement Instruments, and Their Validity Evidence in Randomized Controlled Trials on Virtual, Augmented, and Mixed Reality in Undergraduate Medical Education: Systematic Mapping Review

Abstract: Background Extended reality, which encompasses virtual reality (VR), augmented reality (AR), and mixed reality (MR), is increasingly used in medical education. Studies assessing the effectiveness of these new educational modalities should measure relevant outcomes using outcome measurement tools with validity evidence. Objective Our aim is to determine the choice of outcomes, measurement instruments, and the use of measurement instruments with validity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 133 publications
(389 reference statements)
0
15
0
Order By: Relevance
“…Although previous reviews have focused on motivational design features of web-based instruction in HPE [ 38 , 44 , 49 - 58 ], none have sought to (1) achieve the specific goal of using existing evidence to refine models of motivational design, (2) propose which types of evidence will be required to meet this goal, (3) identify the study designs that can generate such evidence (eg, studies comparing motivational design strategies), and (4) appraise the degree to which studies have generated such evidence. Thus, the value of our review lies in its ability to appraise where we have been and to inform where we ought to go.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous reviews have focused on motivational design features of web-based instruction in HPE [ 38 , 44 , 49 - 58 ], none have sought to (1) achieve the specific goal of using existing evidence to refine models of motivational design, (2) propose which types of evidence will be required to meet this goal, (3) identify the study designs that can generate such evidence (eg, studies comparing motivational design strategies), and (4) appraise the degree to which studies have generated such evidence. Thus, the value of our review lies in its ability to appraise where we have been and to inform where we ought to go.…”
Section: Discussionmentioning
confidence: 99%
“…Studies will also be identified by hand searching the reference lists of previous systematic reviews related to web-based instruction in HPE [ 38 , 44 , 49 - 58 ].…”
Section: Methodsmentioning
confidence: 99%
“…[20] However, MR equipment is not widely distributed yet; therefore, the development of medical education programs using it is limited. [1] Although there are reports of education on the treatment of trauma patients using MR technology, there are cases where it was developed with the goal of learning specific skills rather than the entire process of treating trauma patients. [21,22] This study aimed to examine the educational effect and satisfaction of a tool to learn the entire process of actual trauma patient treatment using MR technology.…”
Section: This Work Was Supported By the National It Industry Promotio...mentioning
confidence: 99%
“…XR technology is subdivided into virtual reality (VR), augmented reality (AR), and mixed reality (MR). [1][2][3] It is classified into whether the head-mountdisplay (HMD) that provides the image delivers only complete digital information (VR) or whether virtual information is overlaid on real information through translucent glass (AR, MR). In addition, virtual information can be directly manipulated by the user (VR, MR), or information can be provided unilaterally (AR).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its role in augmenting and enhancing direct clinical care, the technology has the potential to provide a means to capture, store, and annotate data obtained during routine clinical interactions that may populate digital data repositories to support future clinical care, education, and research. It may also lead to better quality assurance and governance through novel performance and outcome insights . Despite MR’s potential, the technology remains relatively immature and there are important questions concerting its sustainability, scalability, and cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%